Proceedings of the 4th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2014
DOI: 10.7712/120113.4662.c1439
|View full text |Cite
|
Sign up to set email alerts
|

On the Response of the Small Buildings to Vibrations

Abstract: Abstract. In this work, the analysis the response to vibrations of a small building equipped

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The structure is characterized by the stiffness and damping which can be considered to be either the cubic Duffing, cubic-quintic Duffing or Rayleigh, or another such as the Van der Pol with first, second, third, fourth and fifth term. The stiffness is expressed as a sum of a linear and a cubic Duffing term, while the damping is considered to be linear (See [6]).…”
Section: Introductionmentioning
confidence: 99%
“…The structure is characterized by the stiffness and damping which can be considered to be either the cubic Duffing, cubic-quintic Duffing or Rayleigh, or another such as the Van der Pol with first, second, third, fourth and fifth term. The stiffness is expressed as a sum of a linear and a cubic Duffing term, while the damping is considered to be linear (See [6]).…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that when the unsteady wind is present, IPD decreases the amplitude of galloping in all cases of loading, but has no influence on the galloping onset. Notice that the IPD can be introduced via a damper device in the interfloors damping as reported in [13]. Its use as a control strategy was motivated by its simple implementation and beneficial effect in reducing vibration in many engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…The energy source is influenced by the response of the system and consequently, the system exhibits jumps at critical values of the energy source. The system mimics a disappearance of the energy in the resonance regions which can affect the stability of the system, sending it to chaos [2][3][4].…”
mentioning
confidence: 99%